Prionoid Proteins in the Pathogenesis of Neurodegenerative Diseases - Wells, Cameron; Brennan, Samuel E.; Keon, Matt; Saksena, Nitin K. (Frontiers in Molecular Neuroscience, 2019)
There is a growing body of evidence that prion-like protein behaviours are a core element of neurodegenerative diseases (NDs) that afflict humans. Common elements in pathogenesis, pathological effects and protein-level behaviours exist between Alzheimer’s Disease, Parkinson’s Disease, Huntington’s Disease and Amyotrophic Lateral Sclerosis. These extend beyond the affected neurons to glial cells and processes. This results in a complicated system of disease progression, which often takes advantage of protective processes to promote propagation of pathological protein aggregates. This review provides a current snapshot of knowledge on these proteins and their intrinsic role in the pathogenesis and disease progression seen across NDs.